Proceedings of the Ocean Drilling Program 1990
DOI: 10.2973/odp.proc.sr.115.131.1991
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Geochemistry of Leg 115 Basalts and Inferences on the History of the Réunion Mantle Plume

Abstract: Strontium, neodymium, and lead isotope ratios are reported for 13 Leg 115 basalts as well as 3 basalts from Texaco drill hole SM-1 on the Mascarene Plateau. Pb ratios, typical of Indian Ocean mid-ocean ridge (MORB) and oceanic-island basalts (OIB). Isotopic compositions of Leg 115 basalts generally fall between fields for MORB and Reunion Island basalts, consistent with the conclusion drawn from geochronological studies that Deccan flood basalt volcanism, the Chagos-Laccadive Ridge, and the Mascarene Plateau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Values for the youngest drill site, Site 706 (33 Ma), are closest to those of Mauritius and Réunion. White et al (1990) argued that, as a group, the ε Nd values of the Leg 115 basalts and Réunion showed an overall decrease, and 87 Sr/ 86 Sr a rough increase, with decreasing age. Within the framework of the mantle plume model for ocean island volcanism (e.g., Richards et al, 1989), they interpreted this trend as reflecting progressively decreasing entrainment of asthenospheric (MORB-source) mantle by the upwelling plume.…”
Section: Nd-sr Isotopesmentioning
confidence: 97%
See 2 more Smart Citations
“…Values for the youngest drill site, Site 706 (33 Ma), are closest to those of Mauritius and Réunion. White et al (1990) argued that, as a group, the ε Nd values of the Leg 115 basalts and Réunion showed an overall decrease, and 87 Sr/ 86 Sr a rough increase, with decreasing age. Within the framework of the mantle plume model for ocean island volcanism (e.g., Richards et al, 1989), they interpreted this trend as reflecting progressively decreasing entrainment of asthenospheric (MORB-source) mantle by the upwelling plume.…”
Section: Nd-sr Isotopesmentioning
confidence: 97%
“…Data sources for Mauritius are this study, Mahoney et al (1989), and Peng and Mahoney (1995). Fields for CIR and Carlsberg Ridge MORB (Ito et al, 1987;Mahoney et al, 1989) and Réunion (Fisk et al, 1988) are shown for comparison, as are data for ODP Leg 115 and Texaco drill site SM-1 (White et al, 1990). Ages for the Leg 115 and SM-1 basalts are from Duncan and Hargraves (1990). post-shield Intermediate and Younger Series lavas of Mauritius are more MORB-like in Nd-Sr isotopic characteristics than the shield-stage Older Series, it is possible, perhaps likely, that the drill-site lavas represent post-shield volcanism and that shieldstage lavas were not penetrated during drilling.…”
Section: Nd-sr Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cretaceous basalts also occur along the southeast Madagascan coast, with instead more radiogenic isotopic compositions of ε Nd = +4.6 ± 3.0 (2σ, n = 3) (Mahoney et al, 1991). The geology of the Mascarene Plateau is varied and Nd isotope measurements are available from southern Mascarene Plateau volcanics with ε Nd = +6.3 ± 1.6 (2σ, n = 8) (White et al, 1990) and Reunion Island volcanics with ε Nd = +3.1-4.5 (Bosch et al, 2008). In the global compilation of Jeandel et al (2007), the margin of the western Indian Ocean in this region is assigned a value of ε Nd = -14, but this clearly represents an average of old continental crustal sources and younger volcanics rather than a uniform source of this composition.…”
Section: Regional Setting and Hydrographymentioning
confidence: 99%
“…Lawver & Gahagan, 1993) (slightly before the 150 Ma Masiran origin of the 120 Ma Masiran rocks remains problematic, because although the isotopic signature of the main rocks were formed), and northward flow of Indian-Oceantype mantle may have begun earlier there. If so, to reach component in the Réunion plume appears to have changed little in the last 66 my (White et al, 1990; Peng the paleolatitude of the Samail crust by 95 Ma, such asthenospheric flow must have occurred at rates of~70-& , the Réunion hotspot is believed by most workers to have appeared only shortly before 66 100 mm/yr; in comparison, rates of 25-40 mm/yr are indicated for westward flow of Pacific-type asthenosphere Ma, the Deccan Traps event being interpreted as the hotspot's initial, plume-head phase [e.g. Basu et al (1993) into the southeastern Indian Ocean between Antarctica and Australia since 43 Ma (Pyle et al, 1992(Pyle et al, , 1995.…”
Section: Western Indian Ocean Drill Sitesmentioning
confidence: 99%